Diabetes is a strong predictor of mortality during tuberculosis treatment: a prospective cohort study among tuberculosis patients from Mwanza, Tanzania. Issue 7 (6th May 2013) - Faurholt‐Jepsen, Daniel; Range, Nyagosya; PrayGod, George; Jeremiah, Kidola; Faurholt‐Jepsen, Maria; Aabye, Martine G.; Changalucha, John; Christensen, Dirk L.; Grewal, Harleen M. S.; Martinussen, Torben; Krarup, Henrik; Witte, Daniel R.; et al.
Abstract Objective Strong evidence suggests diabetes may be associated with tuberculosis (TB) and could influence TB treatment outcomes. We assessed the role of diabetes on sputum culture conversion and mortality among patients undergoing TB treatment. Methods A total of 1250 Tanzanian TB patients were followed prospectively during TB treatment with sputum culture after 2 and 5 months. Survival status was assessed at least 1 year after initiation of treatment. At baseline, all participants underwent testing for diabetes and HIV, and the serum concentration of the acute phase reactant alpha‐1 glycoprotein (AGP) was determined. Results There were no differences between participants with and without diabetes regarding the proportion of positive cultures at 2 (3.8% vs. 5.8%) and 5 (1.3% vs. 0.9%) months (P > 0.46). However, among patients with a positive TB culture, relatively more patients with diabetes died before the 5‐month follow‐up. Within the initial 100 days of TB treatment, diabetes was associated with a fivefold increased risk of mortality (RR 5.09, 95% CI 2.36; 11.02, P < 0.001) among HIV uninfected, and a twofold increase among HIV co‐infected patient (RR 2.33 95% CI 1.20; 4.53, P = 0.012), while diabetes was not associated with long‐term mortality. Further adjustment with AGP did not change the estimates. Conclusion Diabetes considerably increases risk of early mortality during TB treatment. The effect may not be explained by increased severity of TB, but could be due to impaired TB treatment response. Research is needed to clarify the mechanism and to assess whether glycaemic control improves survival.